Specifically Regulated Pesticides in Florida - Methyl Bromide - Frederick M. Fishel (EDIS)
PI-157, a 3-page illustrated fact sheet by Frederick M. Fishel, describes this hydrocarbon fumigant, which is specifically regulated in Florida, its effective dates, applicator requirements, application equipment, safety equipment, exemptions, and additional information. Published by the UF Agronomy Department, October 2007.